Pemahaman Umat Tentang Musik Liturgi di Stasi St. Yosef Kampung Baru - Lorensius Amon; Wilfridus Samdirgawijaya (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2017)
The results of this research show that the comprehension of the Catholics at the Church-station of St. Yosef Kampung Baru about the liturgical music is a comprehension of relating aspects of faith, ritual and mood. Faith is the base of and aim for the rituals and mood orientation. Faith reveals the mistery of Christ in the forms of prayers, hymns of praise, expressions of gratitude, and divine words. Rituals are forms of and means for presenting and experiencing faith. Rituals are purposively structured in such a way that the faith on God is expressively revealed in the rituals. Mood is the psychological condition enabling faith to be experienced and conceived in the rituals. Mood orientation could create the liturgy to be more lively, exalted and solemn through the liturgical music accompanying the activities and the services. Expression of faith needs the rituals as forms of and means for presenting the faith. Faith needs mood orientation as the psychological condition for experiencing faith. Rituals also need mood orientation as psychological condition which enables the rituals to be religious rituals expressing the faith. The rituals need faith as the base of and aim for the rituals. Mood orientation on the other hand needs the rituals as means for its realization. Mood orientation also needs faith as its aim which gives identities to the mood created. Therefore, the comprehension of the Catholics at the Church-station of St. Yosef Kampung Baru about the liturgical music is a comprehension of the aspects of faith, ritual and mood which are related to each other and mutually needed.